(untitled) (Scientific journal of the Fergana State University, 2024)
Due to the fact that the land was considered the main source of income for the population in the Khiva Khanate, during this period specific procedures for dealing with the land and any actions related to it were created. Especially in the period under study, the issues related to land and farming have risen to the level of state policy. In order to have certain ideas about the socio-economic life of the Khanate of Khiva, first of all, it is necessary to determine the order of land ownership in this area. This article analyzes issues related to the system of land ownership in Khiva Khanate.